PERANAN KOPERASI MAHASISWA DALAM MEMBENTUK MENTAL ENTERPRENEURSHIP MAHASISWA - Munawar Thoharudin (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
This study aimed at determining the role of student’s cooperatives in building the entrepreneurial mentality on the students of Economics Education STKIP Persada Khatulistiwa Sintang. The method of the research used was qualitative approach. The data of the research were obtained from two sources namely: Primary data and Secondary data. Data collection techniques used in this study was interviews, observation and documentation. The data collecting instruments used was interview guidelines, field notes and researchers themselves. Data analysis was done through data reduction, data presentation, and conclusion. Based on the results of the research, obtained that: 1) The role of the student’s cooperatives seen from 2 approaches, that are Student’s Cooperative as entrepreneurial education unit trains and educates students in cooperative management as well as train and educate students in developing entrepreneurial potential. 2) The role of student cooperative in building students' entrepreneurial mentality at Kopma on Economics Education of STKIP Persada Khatulistiwa Sintang has been appropriate for indicators of entrepreneurial mentality in terms of leadership, task and result oriented, future orientation, creativity, risk-taking and self-confidence.